Optimizing the performance of a paper mill effluent treatment - ElSergany, Moetaz; Amimul Ahsan,; Md. Maniruzzaman A. Aziz, (Universiti Kebangsaan Malaysia, 2015)
The paper making industry is characterized by high rate of water consumption and hence high rate of wastewater generation. The purpose of this research was to assess and optimize the existing complete mix activate sludge treatment plant that is used to treat the high strength paper mill effluent with the highest possible efficiency at a reasonable cost. The collected paper mill wastewater is equalized in an equalization tank before being pumped to the treatment plant. The treatment plant includes chemical treatment unit, complete mix activated sludge and granular media filtration unit. The results showed that effluent of a chemical treatment unit was found to be relatively similar to the laboratory simulated plain sedimentation unit. It can be concluded that addition of chemical coagulant can be eliminated with an overall saving of chemical addition costs. The complete mixing activated sludge achieved good removal of biochemical oxygen demand (BOD) and chemical oxygen demand (COD). Furthermore, the results showed that the plant is operated under low BOD:P ratio. The treatment efficiency of the plant can be improved by increasing the phosphorous dose to the plant to have BOD:P ratio of 100:0.5 to 100:1. It was found that 50% of the treated effluent is recycled to the manufacturing process, however this percentage can be increased through proper plant optimization and control of nutrient addition to the activated sludge unit.